Biotransformation of balanocarpol using different fungi from the Malaysian forest / Muhammad Kaleem Shaunawaaz Jeehoo - Jeehoo, Muhammad Kaleem Shaunawaaz (2009)
Biotransformation has been a subject of interest since centuries ago. It can be used to modify a compound into another compound, which may be hard to obtain during chemical synthesis by using microorganisms such as endophytes. The study is aimed to identify the biotransformation product using a given substrate which is known as Balanocarpol by using fermentation with 3 different microorganisms namely Asperlligus niger (ATCC), Asperlligus (HAB10R12 endophyte) and Botrytis cinerea to rationalize the chemical modification induced by them and compare with standard organic chemistry procedure. Overall methodology includes media preparation, inoculating of the fungi into different media, feeding of substrate, incubating them for one to two weeks, then extracting with EtOAc. Finally the extract was analyzed by using High Performance Liquid Chromatography (HPLC) technique to determine the biotransformed products.